1995
DOI: 10.1016/0029-7844(95)00252-m
|View full text |Cite
|
Sign up to set email alerts
|

Rate of hospitalization for gynecologic disorders among reproductive-age women in the United States

Abstract: Our findings confirmed the importance of PID as a common cause of hospitalization among reproductive-age women and identified additional gynecologic conditions as causes for hospitalization as well. We found significant age and racial differences not only among women with discharge diagnoses of PID but also among those with discharge diagnoses of uterine leiomyomas and endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 2 publications
3
75
0
3
Order By: Relevance
“…An increase with age in the prevalence of fibroids during the reproductive years has been demonstrated by several epidemiologic studies (Marshall et al 1997;Ross et al 1986;Velebil et al 1995;Wilcox et al 1994). Studies that define cases by pathologic diagnosis, thus restricting cases to those having surgery (Ross et al 1986), have shown a rapid increase in fibroid diagnoses among women in their forties.…”
Section: Agementioning
confidence: 98%
“…An increase with age in the prevalence of fibroids during the reproductive years has been demonstrated by several epidemiologic studies (Marshall et al 1997;Ross et al 1986;Velebil et al 1995;Wilcox et al 1994). Studies that define cases by pathologic diagnosis, thus restricting cases to those having surgery (Ross et al 1986), have shown a rapid increase in fibroid diagnoses among women in their forties.…”
Section: Agementioning
confidence: 98%
“…This is in contrast to a study conducted 20 years ago using National Hospital Discharge Survey data that found rates of hospital discharges for menstrual disorders were greatest among women ages 40-44 years and rates of menstrual disorders for non-white women were higher than rates for White women, though this difference was not statistically significant. 16 However, the earlier study focused on hospitalization for menstrual disorders and should be interpreted cautiously within the context of current medical practices. Hospitalizations for AUB for women not undergoing hysterectomy have decreased dramatically over the past few decades, 15 and although women with AUB may be younger, they may be less likely to need hospitalization for their problem.…”
Section: 4mentioning
confidence: 99%
“…Between 1990 and 1998, it was the third most common gynecological diagnosis listed in the hospital discharge summaries of women aged 15 to 44 years. 22 Endometriosis results in lost productivity, hospitalizations, and surgical procedures, as well as outpatient and prescription drug costs. Many women resort to bed rest during bouts of endometriosis-related pain, with almost half the women with endometriosis in one study reporting the need for an average of 17.8 days of bed rest in the previous 12 23 The aims of endometriosis treatment are to eliminate symptoms, reduce the process of inflammation, and limit tissue destruction that might result from long-standing disease.…”
Section: Actuarial Analysis Of Private Payer Administrative Claims Damentioning
confidence: 99%